ANALYSIS OF THE FINANCIAL PERFORMANCE OF THE KUPANG CITY REGIONAL GOVERNMENT - Utami, Sri Endar; Wulandari, Agusta Amanda; Gah, Tiffany N. P. (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The implementation of regional government is based on the principle of regional autonomy. The implementation of local government is also marked by the change in the system from centralization to decentralization which is directed at accelerating the realization of the welfare of the Indonesian people. Therefore, each region is required to be more independent in managing and managing its government affairs, including in managing regional finances. One of the vital cycles in regional financial management is reporting carried out at the end of each accounting period, in the form of local government financial reports (LKPD). LKPD can be used as a means of conducting performance analysis so that it can increase the role of financial reports themselves. Therefore, the author will conduct more in-depth research to determine the performance of the Kupang City Regional Government over the last 5 years. Design/methodology/approach: This research uses a quantitative descriptive approach. The data collection method will be carried out with documentation. The data is a Budget Realization Report contained in the BPK Audit Results Report for 2018-2022. Findings: The data is then analyzed using financial ratio analysis in the form of regional financial independence ratios, regional financial dependence ratios, degree of decentralization ratios, ratios of effectiveness of regional original income, ratios of regional financial efficiency, harmony ratios and growth ratios. The results of the study stated that the role of the central government was more dominant in financing the administration of the Kupang City regional government, the financial dependence of the local government on the center in the form of transfer income during the last 5 years was very high, the percentage of local original income was less when compared to the total income, the effectiveness of regional original income during The last 5 years have been quite effective. local governments need quite large funds and even increase yearly as long as they finance government operations, but capital expenditures are decreasing yearly. On the other hand, revenue growth from 2018 to 2022 tends to decrease, while the growth in operating expenditures and capital expenditures has fluctuated over the past 5 years. Therefore, the Regional Government of Kupang City is expected to maximize the revenue potential in the region. This is to reduce the dominance of the central government in financing the implementation of the Kupang City Regional Government. Paper type: Research Paper